Aloe vera extract as a burn treater - Yulia Dalfaedah; Evita Dora Sinukaban (Institute of Computer Science (IOCS), 2022)
The aloe vera plant belongs to the Liliaceae family, has considerable potential as a raw material for natural medicine. Aloe vera contains various active substances that can cure various diseases, one of which is for healing burns. This study aims to determine the stability of aloe vera extract cream (Aloe vera) and find out the effect of the fastest healing of burns on infunded mice is extraction by boiling, at a temperature of 45-70°C for 10 minutes which is used to extract active substances that dissolve in water. from vegetable ingredients, by blending aloe vera meat and heating it. Then make several variations for making cream with variations of 10%, 15% with and without Virgin Coconut Oil (VCO). Based on the results of the research test, the results of the examination of the phytochemical identification of aloe vera extract positively contained tannins, phenols and saponins. At the pH of the aloe vera extract cream, the results of examining the pH of the cream obtained a pH ranging from 5-6, so it is safe to use on human skin because the skin's pH ranges from 4.2-6.5. Aloe vera extract and VCO which are formulated in the form of a stable cream within 8 weeks of storage. The results of the burn test from aloe vera extract showed an effect as a medicine for burns where a healing process was seen which was marked by a faster reduction of wounds in mice wounds with a diameter of +1 cm. In this study the FIB formula healed wounds faster at 8 days than the FOB formula within 9 days, the F1A formula took 12 days and the FOA healed on day 14. The FIB formula indicates the fastest time in healing burns with a time of 8 days